Metamorfosis Kupu-kupu dalam Menciptakan Karya Seni Grafis Cetak Tinggi (Relief Print) - Amnah, NurHaniifah; Ariusmedi, Ariusmedi (Al-DYAS, 2023)
The creation of this work aims to visualize Butterfly Metamorphosis in graphic art. The method of creation in this final work is carried out in stages, starting from the preparatory stage of observing natural or environmental phenomena that are happening directly. And then the elaboration (exploring stage), the synthesis stage (idea determination), then the realization of the concept that prepares the sketches, tools and materials, the process of making the work. The last stage is the completion or finishing stage of the work, using the relief print method with different sizes based on the theme of natural phenomena with the idea of Butterfly Metamorphosis in Creating High Print Graphic Art Works (Relief Print) which was developed under the title, "Process" (52x41cm ), “Change” (51x45cm), “Patience” (67x51cm), “Struggle” (60x41cm), “Freedom” (60x41cm), “Beauty” (52x41cm), “Image” (52x41cm), “Fragile” (52x41cm) , “Love” (52x41cm), “The Cycle of Life” (52x41cm).